The Nuclear Structure for Exotic Neutron-Rich of 42, 43, 45,47K Nuclei (Baghdad Science Journal, 2016)
In this paper the proton, neutron and matter density distributions and the corresponding root mean square (rms) radii of the ground states and the elastic magnetic electron scattering form factors and the magnetic dipole moments have been calculated for exotic nucleus of potassium isotopes K (A= 42, 43, 45, 47) based on the shell model using effective W0 interaction. The single-particle wave functions of harmonic-oscillator (HO) potential are used with the oscillator parameters b. According to this interaction, the valence nucleons are asummed to move in the d3f7 model space. The elastic magnetic electron scattering of the exotic nuclei 42K (J?T= 2- 2), 43K(J?T=3/2+ 5/2), 45K (J?T= 3/2+ 7/2) and 47K (J?T= 1/2+ 9/2) investigated through Plane Wave Born Approximation (PWBA). The inclusion of core polarization effect through the effective g-factors is adequate to obtain a good agreement between the predicted and the measured magnetic dipole moments.